Penambahan Sensor Arduino Uno Pada Mesin Perajang Singkong dan Pisang Berkapasitas 60 kg/Jam - Fadillah, Muhammad Afif; Siregar, A Marabdi; ., Mulyadi; Sembiring, Jesayas (Fakultas Teknik UMSU, 2024)
In the industrial world, machines are widely used to facilitate a more effective and efficient way of working, by trying to abandon old work patterns that rely heavily on human labor along with the development of industrial technology 4.0 in observations made by researchers at household MSMEs in the snack food industry, in Titi Village Payung, Air Putih District, Batu Bara Regency. Processors of cassava and banana chips still use human power and use simple tools. The process of chopping cassava and banana chips is not done at a table, but is done directly on the floor. The chopping process in this condition causes an uncomfortable working position for the worker, because it is done with a bent back position, the head is always bowed and the legs are always bent. . This chopping process is usually carried out for 8 hours per day. The cassava and banana chopper tool at the research site's MSMEs has dimensions of 30 cm long, 15 cm wide and 21 cm high. On this basis, researchers consider it necessary to minimize the obstacles faced by cassava and banana chip managers, by making a cassava and banana chopping machine. The performance test results of the cassava and banana chopping machine obtained 1 kg of cassava and banana slices in 1 minute or the same as 60 kg in 60 minutes, with the resulting cassava and banana slices having a thickness of 1 - 2 mm. This cassava and banana chopping machine has been made to be more practical to use and can compete with domestically made products.